An Exploratory Study of Service Quality, Corporate Image, and Customer Loyalty in Restaurants in Ghana (International Journal of Scientific Research and Management (IJSRM), 2018)
The aim of the study is to identify the effect ofService Quality and Corporate Image on Customer’s Loyalty .Questionnaires were distributed to collect responses from restaurant users in the Greater Accra region of Ghana. Descriptive statistics and correlation analysis were used to analyze the data and draw the conclusions. It was revealed that service quality and corporate image have strong positive association with customer’s loyalty .The study suggested that managers of restaurants provide needed logistics to aid frontline staff to avoid delays in meeting customer demands. This will lead to high level of customer retention,loyalty, high market share and profitability.